Environmental treaties’ impact on the environment in resource-rich and non-resource-rich countries - Zakari, Abdulrasheed; Adedoyin, Festus Fatai; Taghizadeh-Hesary, Farhad; Pazouki, Azadeh (Environmental science and pollution research international, 2021)
This paper examines the impact of environmental treaties on the environment across 74 countries: 50 resource-rich and 24 non-resource-rich countries. Using data spanning over 35 years, we find a negative and significant association between environmental treaties and environmental quality in resource-rich countries. On the contrary, we find environmental treaties positively and significantly affect the environment in non-resource-rich countries. Our results suggest that the environmental treaties signed by resource-rich countries may lead them to achieve sustainable development growth by 2030. Therefore, our results extend the environment literature and inform policymakers of the need to pay attention to the effects of signing environmental treaties on environmental protection.